Weaving a greener future: The impact of green human resources management and green supply chain management on sustainable performance in Bangladesh's textile industry - Syed Ridoy Ali; Abdullah Al masud; Md. Alamgir Hossain; K.M. Zahidul Islam; S.M. Shafiul Alam (Cleaner Logistics and Supply Chain)
The purpose of this study is to investigate the impact of Green Human Resource Management (GHRM) and Green Supply Chain Management (GSCM) on the sustainable performance of the Bangladeshi textile sector. Specifically, the study focuses on environmental and employee-related aspects. Additionally, we examine how environmental performance and employee performance mediate the relationship between GHRM and GSCM. This study draws upon data collected from 450 employees across various textile enterprises in Bangladesh. Structural Equation Modeling is employed using the Amos 24 software to analyze the relationships and interactions among these variables. These findings demonstrate that using environmentally sustainable practices in human resource management and supply chain management results in enhanced sustainability. The study indicates that environmental performance significantly influences the relationship between GHRM and GSCM regarding sustainable performance. The study findings indicate that firms operating in the textile industry should implement GHRM and GSCM practices to enhance their sustainability performance. Additionally, it is recommended that these organizations prioritize the well-being and engagement of their employees. Implementing such a strategy can bolster the organization's comprehensive sustainability initiatives and raise its standing among stakeholders. This study contributes to the expanding body of literature on textile sustainability by investigating the mediating role of employee and environmental performance. It emphasizes the significance of GHRM and GSCM techniques in improving sustainable performance. The findings provide valuable insights for firms seeking to develop more effective sustainability initiatives.